The Drainage Design on Umban Sari Street from STA 0+500 until STA 0+750 Rumbai Sub-District Pekanbaru City - Fadli Gunawan; Virgo Trisep Haris; Muthia Anggraini (JURNAL TEKNIK UNILAK, 2020)
Drainage is an important part of city building. Drainage’s function is to channel the water stream in order to prevent pudde on road surface which will harm the road construction. Therefore, an adequate drainage is needed to contain the rainwater and waste discharge and channel it to the sewer. The purpose of this research is to calculate the appropriate and adequate canal drainage capacity and dimension so that puddles and floods will less likely to happen in the next 10 years on the research sector. Methods used is gumbel, arithmetic and rational. The result of research is economical section’s trapezoidal drainage design which dimension needed is H = 1,14 m. B = 1,41 m, T = 2,55 m and w = 0,75 m. Therefore can be concluded that designed drainage capacity plan on sector Umban Sari street is capable to contain rainwater discharge, because it adjusted to total discharge plan of 0,55509 m3/s and total discharge plan of 0,246 m/s. The suggestion from this research so that this planned drainage can function optimally is all party concerned will have to maintenance the drainage periodically, by doing checking, cleaning and not littering.